2009
DOI: 10.1108/00197850910950952
|View full text |Cite
|
Sign up to set email alerts
|

Using the DiSC® model to improve communication effectiveness

Abstract: PurposeThe purpose of this paper is to provide an explanation of the DiSC personality model along with a real‐world example of its effectiveness.Design/methodology/approachThe DiSC personality model explores people's communication priorities and how those priorities influence behavior. Kudu Industries is one company that has successfully implemented DiSC throughout the company, and this paper serves as an example of the model's use within an organization.FindingsEvery individual within an organization has uniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…The DiSC personality model is a lesser known model than the MBTI. As such, we found few studies by psychologists, and most of the independent research existing on the DiSC personality model is industry research, where they study what kind of personality is successful or how to use personality to increase cooperation between employees [Reynierse et al, 2000;Sugerman, 2009]. This means that we have only a vague idea of how reliable the DiSC personality model is and of how doable personality extraction is with that model.…”
Section: Discmentioning
confidence: 99%
See 1 more Smart Citation
“…The DiSC personality model is a lesser known model than the MBTI. As such, we found few studies by psychologists, and most of the independent research existing on the DiSC personality model is industry research, where they study what kind of personality is successful or how to use personality to increase cooperation between employees [Reynierse et al, 2000;Sugerman, 2009]. This means that we have only a vague idea of how reliable the DiSC personality model is and of how doable personality extraction is with that model.…”
Section: Discmentioning
confidence: 99%
“…As mentioned in Section 1.1.3, there are few studies validating the DiSC personality model. There are reports by companies providing DiSC training showing that it is a valid personality model [noa, 2013], and industry research talking about the use of DiSC in the professional world [Reynierse et al, 2000;Sugerman, 2009], but no independent study working on the DiSC personality model from the psychology point of view was found. As such we had, when starting the project, no real idea of how well personality extraction would work with the DiSC personality.…”
Section: Voting Systemmentioning
confidence: 99%
“…For this purpose, a tool that assesses the individual and the role she will have inside a team was needed. After reviewing the available tools for such a purpose [3], the DISC (dominance, inducement/influence, submission/steadiness, compliance) tool [39] was chosen for 4 reasons: 1) DISC is more flexible than other tools since it requires a rather small amount of people per team (only four), 2) DISC has been successfully used recently to assess the personalities of members of collaborating teams and study team performance [11,40], 3) DISC is widely used in human resources management due to its practicality and tangible outcomes [40,41], 4) DISC is a reliable and valid tool based on recent studies [42]. The latter reason is of importance since the present work aims at applying research outcomes to real work settings and thus targets actual organizational issues.…”
Section: Literature Reviewmentioning
confidence: 99%
“…• Dominance: The way people deal with problems and control situations. With the current personality classification it is possible to locate relations between people themselves, and between people and tasks, leading to improvements in work productivity, as well as teamwork and development of communication skills [27][28][29]. In parallel, research is done using the same personality test in order to make prediction about group format, member's satisfaction and performance of tasks [30].…”
Section: Personality Testmentioning
confidence: 99%